Investigation of crystal structure and chemical bonds characteristics on microwave properties of novel Ca-doped Sr1–xCaxTm2O4 (x=0.025–0.300) ceramics - Wenjie Zhang; Yanjun Liu; Guoqiang He; Ziqi Zhao; Yuan Nie; Yiwen Ma; Fangyi Huang; Huanfu Zhou (Journal of Materiomics)
Dense microwave dielectric ceramics of Sr1–xCaxTm2O4 (x = 0.025–0.300) were fabricated via the conventional solid-state reaction method. Systematical investigations on the impact of Ca2+ on their microstructures, sintering behaviors, and microwave dielectric properties were detailly conducted. The combined XRD data and subsequent refinement demonstrated that all samples exhibited structural conformity with SrTm2O4 and belonged to Pnam space group. Calculations were executed to illustrate the evolution of performance-related chemical bonding parameters associated with Ca2+ on the basis of the PVL theory. High density, lattice energy and narrow full width at half maximum of Raman modes contribute to a performance boost of around 14%. Excellent dielectric properties of Sr0.95Ca0.05Tm2O4, including relative permittivity of 15.97, quality factor of 47,142 GHz, and temperature coefficient of resonant frequency of −24.65 × 10−6 °C−1. Furthermore, Sr0.95Ca0.05Tm2O4 ceramics were designed as rectangular dielectric resonator antennas with 388 MHz bandwidth at the center frequency of 6.525 GHz, along with high simulated radiation efficiency (≥90%) and realized gain (5.80–6.47 dBi), which suggests their considerable potential in 5G communication applications.